STUDI KOMPARATIF SEJARAH PERADILAN MILITER DI INDONESIA DENGAN PERADILAN ANGKATAN BERSENJATA DI MALAYSIA - Gunawan Widjaja; Wagiman Martedjo; Sudrajat Mukti Nugroho (LPPM STIH Awang Long, 2025)
The military court system in Indonesia is the implementation of judicial authority within the military to enforce just and fair legal proceedings. (See: Selected Cases in Military Court Proceedings. https://dilmil-aceh.go.id/tentang-peradilan-militer/) Meanwhile, the military court system in the Kingdom of Malaysia is a military judicial institution that forms part of the integrated military power structure. It also carries out the task of safeguarding the integrity of the territory and sovereignty of the Kingdom of Malaysia, protecting it from various threats and disturbances from within and without. This research uses the normative legal method. The results of this research reveal fundamental differences between the military court system in the Republic of Indonesia and that of the Kingdom of Malaysia. The military justice system in the Republic of Indonesia is an independent system, not part of the general justice system. This is because it has the primary duty of maintaining integrity; protecting and defending the sovereignty of the nation and state. Meanwhile, the military court of the Armed Forces of the Kingdom of Malaysia has the responsibility of supporting civil authority in countering international disturbances, maintaining public order, handling natural disasters, and participating in national development programmes.